2020
DOI: 10.32583/keperawatan.v12i4.1034
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Family Support and Stress with the Quality of Life of the Elderly Type II Diabetes Mellitus

Abstract: Diabetes is a serious chronic disease that occurs because the pancreas does not produce enough insulin. Quality of life is very important to get serious attention, because the quality of life is something that is closely related to a person's health condition, the severity of the disease, the duration of healing, and can even aggravate the condition of the disease to death if a person has a poor quality of life. This study aims to determine the relationship between family support and stress with the quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
0
0
1
Order By: Relevance
“…A study conducted by (Erda et al, 2020) revealed that there was a significant relationship between stress and the quality of life among elderly people with type II diabetes mellitus 24 . Poor quality of life was due to the patient's perception of the disease in terms of recovery.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by (Erda et al, 2020) revealed that there was a significant relationship between stress and the quality of life among elderly people with type II diabetes mellitus 24 . Poor quality of life was due to the patient's perception of the disease in terms of recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Perawat juga dapat berperan sebagai care provider dengan cara melakukan pengkajian untuk mengetahui sumber dari dukungan keluarga dan penghalang yang dapat muncul dalam pemberian dukungan keluarga (Erda et al, 2020). Pasien dengan penyakit DM dituntut untuk dapat beradaptasi dengan penyakitnya sehingga dapat mengatur dan menangani perubahan pola hidup yang terjadi pada dirinya sehingga dapat mengubah perilaku dirinya dari perilaku maladaptif ke perilaku adaptif.…”
Section: Pendahuluanunclassified
“…Tiga tahap ini berbeda baik secara biologis, maupun psikologis. Memasuki usia tua berarti mengalami kemunduran, misalnya kemunduran fisik, yang ditandai dengan kulit yang mengendur, rambut memutih, gigi mulai ompong, pendengaran kurang jelas, penglihatan semakin memburuk, gerakan lambat dan figur tubuh yang tidak proporsional (Erda et al, 2020).…”
Section: Masalah -Masalah Pada Lansiaunclassified